ANALISIS STRATEGI PQ4R DENGAN PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR SISWA PADA TOPIK ALJABAR - Mohammad Archi Maulyda; Asri Fauzi; Lalu Hamdian Affandi; Linda Feni Haryati; Siti Istiningsih (IKIP Siliwangi, 2020)
The use of the lecture method causes low participation, student progress, student attention, and interest cannot be monitored. The inactivity of students during the learning process is one of the factors that can cause students to difficult to understand the concept of material. If this happens it can result in less than optimal learning outcomes obtained. The type of research used is True-experimental Design with Pretest-Posttest control group Design type. The independent variable in this study is the PQ4R model with a scientific approach. While the dependent variable is learning outcomes. The population in this study were students of class VIII. The sample of this research is a class of 25 students. Determination of the sample using a cluster type random sampling technique. Data collection instruments include lesson plans, observation sheets of student activities, observation widths of teacher activities, pre-test, and post-test learning outcomes. The data analysis technique used an independent sample t-test which was previously tested by the Kolmogorov-Smirnov method with the help of SPSS for windows version 17.0. The results showed: (1) The teacher can carry out PBM activities well and in accordance with the learning plan in accordance with the syntax. (2) Student activities are in accordance with what is expected from the frequency of the many activities that illustrate PBM with the PQ4R strategy with a scientific approach. This shows that the PQ4R strategy can affect student learning outcomes